Records Management at the Amuntai Religious Court Class I-B Office, Hulu Sungai Utara Regency - Mahrini, Mahrini; Hidayatullah, Syarif; Utami, Sri; Aprilia, Nining (CV. Publikasi Indonesia, 2025)
This study addresses critical deficiencies in human resources, archival systems, and infrastructure. Employing a qualitative descriptive approach, data were collected from 12 purposively selected informants through interviews, observations, and documentation, validated via prolonged observation, persistent engagement, and triangulation. Findings reveal significant gaps in three dimensions: human resources (staff lack specialized archival education and training, resulting in limited professional competencies), systemic weaknesses (absence of formal procedures and inadequate facilities), and infrastructure constraints (insufficient storage space without climate control). Despite these challenges, functional strengths include relatively efficient storage systems using simplified classification, satisfactory service delivery, proper borrowing procedures with appropriate protocols, routine maintenance practices, and systematic destruction processes that prevent accumulation. However, critical deficiencies persist: archival personnel lack specialized credentials in archival science, have never received professional training, and work in severely constrained physical environments with narrow storage areas lacking air conditioning, which accelerates document deterioration. Root causes include the organizational undervaluation of archival expertise, insufficient resource allocation, and the absence of professional development frameworks. Recommendations include implementing structured archival training programs, establishing educational prerequisites for archival positions, formalizing standard operating procedures, investing in climate-controlled facilities, and elevating archival management as an institutional priority. These evidence-based interventions would enhance operational efficiency, ensure regulatory compliance under Law No. 43/2009, strengthen institutional memory preservation, and support ongoing judicial digitalization initiatives. Ultimately, these efforts would improve public sector accountability and service quality in Indonesia's religious court system.